"I SEE YOU, I BELIEVE YOU, I STAND WITH YOU": #MeToo and the performance of networked feminist visibility. Issue 3 (3rd April 2021) - Clark-Parsons, Rosemary
ABSTRACT: Hashtag feminism, a form of activism that appropriates Twitter's metadata tags for organizing posts to draw visibility to a cause, has become a central component of the feminist media repertoire. Much discourse about hashtag feminism revolves around whether or not Twitter is an effective tool for activism. This instrumentalist approach leaves activists' strategies for juggling both the affordances and limitations of hashtag feminism under-theorized. Taking up a case study of the #MeToo movement, I consider practitioners' perspectives on hashtag feminism and highlight the processes through which activists develop tactics while working within particular sociotechnical constraints. Through an analysis of a meta-tweets, or tweets about the campaign, I argue that hashtag feminism is a contentious performance in which activists make the personal political by making it visible, bridging the individual with the collective and illustrating the systemic nature of social injustice. As #MeToo demonstrates, however, making the personal visible on a globally networked stage opens activists up to a variety of risks. To address these limitations, #MeToo participants developed performance maintenance strategies, through which they evaluated the campaign's shortcomings and advanced solutions. Their reflexivity points toward hashtag feminism as a complex recursive process aimed at achieving a transformative politics of visibility.